2013
DOI: 10.1088/0004-637x/768/2/144
|View full text |Cite
|
Sign up to set email alerts
|

Wind Braking of Magnetars

Abstract: Considering recent observations challenging the traditional magnetar model, we explore the wind braking of magnetars. There is evidence for strong multipole magnetic fields in active magnetars, but the dipole field inferred from spin down measurements may be strongly biased by a particle wind. Recent challenging observations of magnetars may be explained naturally in the wind braking scenario: (1) The supernova energies of magnetars are of normal value; (2) The non-detection in Fermi observations of magnetars;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 70 publications
(157 reference statements)
3
89
0
Order By: Relevance
“…Observationally, two magnetars 4U 0142+61 and 1E 2259+586 may have fallback disks (Wang et al 2006;Kaplan et al 2009). Timing observations of these two magnetars showed that their surface dipole field are both around or smaller than 10 14 G, depending on the assumed braking mechanism (Tong et al 2013;Olausen & Kaspi 2014). The two observed magnetar/fallback disk systems are consistent with the calculations here 6 .…”
Section: Calculations For Typical Magnetar Parameterssupporting
confidence: 85%
“…Observationally, two magnetars 4U 0142+61 and 1E 2259+586 may have fallback disks (Wang et al 2006;Kaplan et al 2009). Timing observations of these two magnetars showed that their surface dipole field are both around or smaller than 10 14 G, depending on the assumed braking mechanism (Tong et al 2013;Olausen & Kaspi 2014). The two observed magnetar/fallback disk systems are consistent with the calculations here 6 .…”
Section: Calculations For Typical Magnetar Parameterssupporting
confidence: 85%
“…The ray-tracing discussed in Section 2 can be used for rays passing through a pulsar wind, introducing relativistic and plasma effects into models of binary eclipses for a double NS or NS-black hole binary that is nearly edge on with respect to the observer. In the case of an aligned rotator we expect a wind density proportional to 1/r, such that h = 1 (Contopoulos, Kazanas & Fendt 1999;Harding, Contopoulos & Kazanas 1999;Kirk, Lyubarsky & Petri 2009;Tong, Xu, Song & Qiao 2013), shown in Fig. 2.…”
Section: Discussionmentioning
confidence: 97%
“…A physical spin down mechanism must be based on the existence of a magnetosphere [25]. One candidate at present is the wind braking model [80,93].…”
Section: Introductionmentioning
confidence: 99%